Isolation and Complete Capsid Sequence of Enterovirus D111 from Faeces of a Child with Acute Flaccid Paralysis in Nigeria (2019)
The WHO recommended cell-culture-based algorithm requires enterovirus (EV) isolates to produce reproducible cytopathic effect (R-CPE) in RD and/or L20b cell lines. Samples with non-reproducible CPE (NR-CPE) are considered negative for EVs. We investigated whether there could be EVs lurking in samples with NR-CPE. Fifty-nine cell culture supernatants (CCS) (collected between 2016 and 2017) from RD and L20b cell-culture-tubes with NR-CPE, were analyzed. The tubes had been previously inoculated with stool suspension from children (<15 years) in Nigeria with acute flaccid paralysis (AFP). All CCS were screened for Enteric Adenoviruses (EAVs) and group A Rotavirus (GARV) using a rapid immunochromatographic test kit. Subsequently, they were passaged in HEp-2 cell line. All isolates were subjected to RNA extraction, cDNA synthesis, three (5l-UTR, VP1 and EV Species C [EV-C]) different PCR assays and sequencing of amplicons. EVs were further subjected to [‘]Illumina sequencing. All CCS were negative for EAVs and GARVs. Four CCS produced R-CPE in HEp-2 cell line, three of which were positive for the 5l-UTR assay. Of the three isolates, two and none were positive for the VP1 and EV-C assays, respectively. One of the two VP1 amplicons was successfully sequenced and identified as Echovirus 1. Illumina sequencing of the three 5l-UTR positive isolates confirmed the E1 isolate and typed the remaining two as EV-Ds (94 and 111). We describe the first EV-D isolates of Nigerian origin and the first complete capsid sequence of the virus globally. We also show that NR-CPE could sometimes be caused by EVs that do not produce R-CPE in specific cell lines.